A TEST OF HANSEN'S METHOD WITH IRREGULAR BOUNDARIES - Groves, Gordon W. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1970)
Free, long seiches in a rectangular basin were simulated with Hansen's method applied in two ways: (1) with the basin boundaries coinciding with the grid coordinate axes, and (2) with the basin boundaries inclined 45 degrees to the grid axes. There was good agreement between the two cases, and with the theoretical solutions.